(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
he pursuit of effective teaching is a fundamental cornerstone of quality education. This study delves into the realm of behavioral competence among teachers, aiming to understand the key factors that contribute to their effectiveness in the classroom. By examining the areas of planning, instructing, communicating, managing, and evaluating, this exploration sheds light on the multifaceted skills and strategies that teachers employ to create impactful learning experiences. Through an analysis of perceptual differences between teachers and students, as well as the alignment of these competencies with modern educational trends, this study seeks to provide valuable insights into cultivating effective teaching practices. The study’s findings reveal that teachers possess significant competency in planning, instructing, communicating, managing, and evaluating. However, a perceptual gap between teachers and students exists, implying that students perceive teachers as slightly less competent than teachers assess themselves. Particularly, senior high school teachers excel in planning with a strong mean of 4.22, reflecting their commitment to meticulous lesson preparation, understanding student knowledge, and effective assignment handling. This aligns with educational principles emphasizing thorough planning. Additionally, the study underscores teachers’ skill in clear communication and participatory teaching, in line with contemporary educational trends. Furthermore, teachers demonstrate above-average proficiency in evaluation, adeptly creating optimal testing environments, utilizing diverse evaluation methods, and maintaining accurate student records. This underscores the value of continuous assessment and constructive feedback for student learning advancement. It is recommended that upcoming research endeavors further investigate the multifaceted aspects of teachers’ pedagogical competence, particularly emphasizing subject matter expertise and the application of a variety of teaching approaches. In light of the study’s findings, several recommendations can be put forth to enhance the overall teaching and learning experience. Firstly, fostering a Student-Teacher Dialogue is crucial; promoting open conversations between teachers and students regarding their perceived competencies and expectations can effectively narrow the perceptual gap and provide valuable insights for refinement. Secondly, the implementation of robust Professional Development initiatives is essential. Conducting training sessions and workshops focusing on innovative instructional strategies, advanced communication techniques, and a diverse array of assessment methods can greatly assist teachers in continually elevating their teaching methodologies. Lastly, the integration of Technology stands as a promising avenue. Exploring avenues to seamlessly incorporate technology into lesson planning, communication channels, and assessment methodologies can significantly augment teaching effectiveness and student engagement, aligning with the dynamic nature of modern education.